ASGPR‐Mediated Uptake of Multivalent Glycoconjugates for Drug Delivery in Hepatocytes. (2nd March 2016) - Monestier, Marie; Charbonnier, Peggy; Gateau, Christelle; Cuillel, Martine; Robert, Faustine; Lebrun, Colette; Mintz, Elisabeth; Renaudet, Olivier; Delangle, Pascale
Abstract: Liver cells are an essential target for drug delivery in many diseases. The hepatocytes express the asialoglycoprotein receptor (ASGPR), which promotes specific uptake by means of N‐acetylgalactosamine (GalNAc) recognition. In this work, we designed two different chemical architectures to treat Wilson's disease by intracellular copper chelation. Two glycoconjugates functionalized with three or four GalNAc units each were shown to enter hepatic cells and chelate copper. Here, we studied two series of compounds derived from these glycoconjugates to find key parameters for the targeting of human hepatocytes. Efficient cellular uptake was demonstrated by flow cytometry using HepG2 human heptic cells that express the human oligomeric ASGPR. Dissociation constants in the nanomolar range showed efficient multivalent interactions with the receptor. Both architectures were therefore concluded to be able to compete with endogeneous asialoglycoproteins and serve as good vehicles for drug delivery in hepatocytes. Abstract : Hepatocellular hotspot : The asialoglycoprotein receptor efficiently and specifically promotes the endocytosis of glycoconjugates functionalized with N‐acetylgalactosamine units, thus enabling liver targeting. We demonstrated efficient cellular uptake in hepatoma cells for two multivalent chemical architectures derived from cyclodecapeptides or tripods.